2003
DOI: 10.1023/a:1025777029741
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract. Neoclassic economic theory suggests global market integration as a strategy to reduce poverty. In line with this paradigm, an increasing number of developing countries have focused on tourism to generate foreign exchange earnings and to meet rising workforce pressure. Coastlines in particular, have been at the forefront of tourist infrastructure development. The article describes tourism development in the village of Kiwengwa on the east coast of Unguja Island (Zanzibar), Tanzania. It is shown that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…(3) Dubois et al found that the development of tourism has had adverse effects on the atmospheric environment, which should be paid attention to. (4) Gössling (5) and Anisimov and Ryzhenkov (6) believed that laws and regulations should be further improved, and policies for tourism development and environmental protection should be introduced to promote the development of the tourism industry. Holden noted that the development of tourism is closely related to the natural environment and concluded that establishing a strong environmental protection ethics system is necessary to meet the environmental challenges facing the tourism industry's development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Dubois et al found that the development of tourism has had adverse effects on the atmospheric environment, which should be paid attention to. (4) Gössling (5) and Anisimov and Ryzhenkov (6) believed that laws and regulations should be further improved, and policies for tourism development and environmental protection should be introduced to promote the development of the tourism industry. Holden noted that the development of tourism is closely related to the natural environment and concluded that establishing a strong environmental protection ethics system is necessary to meet the environmental challenges facing the tourism industry's development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, we calculated the difference coefficient of index j (a j ) to determine its weight (w j ) [Eqs (4). and(5)].…”
mentioning
confidence: 99%
“…Tourism is viewed, from a neoliberalist point of view, as a positive thing because if well-managed it can support local development while transferring capital from the developed to the developing world (Gössling 2001(Gössling , 2003. However the changes that tourism development creates are complex and consequences are often not visible in the short term (Gössling 2001(Gössling , 2003. In terms of local VC actors, a few traders (28% of the sample) in Unguja benefit financially on a short time scale because they earn higher daily net incomes than traders not connected to this lucrative market.…”
Section: Income Disparity and Distributionmentioning
confidence: 99%
“…Akan tetapi dibalik positifnya tujuan pengembangan pariwisata berbasis komunitas, masyarakat memiliki keterbatasan skill dan pengetahuan professional dalam mengelola usaha baru (Anderson, 2015;Gössling, 2002). Perjalanan mereka dalam upaya mengelola dan mengkapitalisasi sumber daya budaya dan alam untuk meningkatkan tingkat kesejahteraan mereka menjadi satu kajian yang menarik.…”
Section: Pendahuluanunclassified